Exome Sequencing as a Potential Diagnostic Adjunct in Sporadic Congenital Hydrocephalus - Sullivan, William (JAMA Pediatr, 2020)
This study evaluates whole-exome sequencing as a diagnostic tool in a cohort of neurosurgically treated congenital hydrocephalus probands.